A situational analysis of conflict in a fishing village - Sharifah Zaleha Syed Hassan., (Universiti Kebangsaan Malaysia, 1974)
The conflict between the trawler and inshore fisherman is no new phenomenon in the fishing industry of the country. With the introduction of the trawl net as a new technique of fishing, the inshore fishermen who use small gears and fish in the waters three mile beyond the coast find that their livelihood is threatened. This is because the trawler boats damage their apparatus and fish in their areas. The fishermen in the village of Kg. Tanjung Dawai are also involved in the strife. In the village, the conflict situation is complicated because several factors, like racial and political factors, are connected with it. However, an examination of the patterns of conflict in that village shows that there are conflicts of values and interests the latter indicating an intraclass struggle.